2018
DOI: 10.1371/journal.pbio.2005653
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for overhang excision and terminal unwinding of DNA duplexes by TREX1

Abstract: Three prime repair exonuclease 1 (TREX1) is an essential exonuclease in mammalian cells, and numerous in vivo and in vitro data evidenced its participation in immunity regulation and in genotoxicity remediation. In these very complicated cellular functions, the molecular mechanisms by which duplex DNA substrates are processed are mostly elusive because of the lack of structure information. Here, we report multiple crystal structures of TREX1 complexed with various substrates to provide the structure basis for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 58 publications
(107 reference statements)
0
36
0
Order By: Relevance
“…Interestingly, mTREX2 was capable of digesting the double-stranded substrate at a higher concentration (0.4 μM) (Figure 1B). Our results showed that TREX2 exhibits the single-stranded DNA-specific activity at a lower concentration and possesses both single- and double-stranded DNA processing activity at a higher concentration that is similar to those of Exo X (21) and TREX1 (16,21), the E. coli and human homologs of TREX2 (Supplementary Figure S1). The unique catalytic properties of TREX2, Exo X and TREX1 are different from those of other DEDDh exonucleases, such as E. coli RNase T (16,33) which cannot deconstruct the double-stranded DNA structure at the higher concentration of 3 μM (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…Interestingly, mTREX2 was capable of digesting the double-stranded substrate at a higher concentration (0.4 μM) (Figure 1B). Our results showed that TREX2 exhibits the single-stranded DNA-specific activity at a lower concentration and possesses both single- and double-stranded DNA processing activity at a higher concentration that is similar to those of Exo X (21) and TREX1 (16,21), the E. coli and human homologs of TREX2 (Supplementary Figure S1). The unique catalytic properties of TREX2, Exo X and TREX1 are different from those of other DEDDh exonucleases, such as E. coli RNase T (16,33) which cannot deconstruct the double-stranded DNA structure at the higher concentration of 3 μM (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 63%
“…The structure of TREX2 for binding to duplex DNA with long double-stranded region; thus, TREX2 is suitable for participating in the process of duplex DNA with a longer double-stranded region, such as chromosomal rearrangement and maintenance. The interacting region between TREX1 and duplex DNA focuses on the terminal of duplex DNA; thus, TREX1 fits for dsDNA terminal deconstruction in immune controlling and trimming of structural DNAs in various DNA repair pathways (16). In summary, our results highlight the characteristic of TREX2 on the processing of duplex DNA with long double-stranded region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Researchers have noted that mutations in TREX1 gene are associated with several diseases, including AGS, FCL, systemic lupus erythematosus (SLE), retinal vasculopathy with cerebral leukodystrophy, Cree encephalitis, and cryofibrinogenemia. 14,17,18 In 2009, Crow and Rehwinkel evaluated the pathogenesis of AGS for the phenotypic overlap with the manifestations of congenital infection and SLE where type I IFN-mediated immunity is provided by viral and self-nucleic acids, Fig. 3 The frameshift mutation in the exon 2 (c.404_407delCAGC) or (p.Ala81AlafsX6) on TREX1 gene makes an early termination in amino acid production, which would be expected to affect the protein's function.…”
Section: Discussionmentioning
confidence: 99%